THE SPECIAL STOPPING SPACE FOR MOTORCYCLES AT SIGNALIZED INTERSECTIONS IN KEDIRI CITY: JURIDICAL REVIEW - Amelia Okta Ariani; Emi Puasa Handayani; Nur Chasanah (EQUALEGUM International Law Journal, 2023)
Background. Traffic engineering technology is a solution to the problem of decreasing the performance of signalized intersections. Special stopping space at the signalized intersection, motorcycles can safely and easily go directly to the intersection. The research aimed to find out the basis of the law and the possible application of the special stopping space. Research Method. This research was normative research that uses a normative juridical approach, this approach is carried out by examining all laws and regulations that are related to the problem (legal issue) being studied. Findings. The legal basics for a motorbike specialized lift at a signal intersection in the city of Kediri Law number 22 of 2009 concerning road traffic and transportation, and also letters from the minister of public works and public housing. Conclusion. A result of the law implementation of the special stopping space for motorbikes at the intersection of signals in the self-location of the law resulted in the birth of a legal state and the result of the law’s penalty.